Optimalization of Ministries Budget Efficiency by Implementation Of Benchmarking At Budget Baseline Review In Indonesia - Nugroho, Adi; Violita, Evony (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The study aims to analyze the benchmarking application conducted at the stage of the baseline review on Output Detail (RO) in the Budgeting of the Ministry/Agency in the Directorate-General of Budget. The research was carried out by applying a qualitative method of case studies to capture phenomena in the stage of baseline review. Data is collected through interviews, observations, and document scrutiny. Data will be presented with the logic model in applying benchmarking concepts. Research results show that benchmarking can improve the efficiency of Office Services RO by adjusting the composition of RO based on the Ministry of Institutions that are the benchmark. This research is expected to provide an alternative to developing new mechanisms in reviewing Line Ministries’ budget baseline that can be applied to other ROs in budget planning documents. This research is limited to the source of documentation and sources from the units in charge of the planning and maintenance process.